Dear Einstein: scientific disclosure in the scientist's correspondences to children - Joyce Loraine Lopes Cunha; Sheila Alves Almeida (Revista de Ensino de Ciências e Matemática)
Einstein is one of the names with the greatest impact in the scientific field. Furthermore, the physicist corresponded with children from different parts of the world. The documents can be consulted in the book “Dear professor Einstein: Albert Einstein’s letters to and from children”, which is precisely the corpus of this investigation. Focusing on the scientific theme, the central objective of the research is to analyze the textual discursive strategies used by the scientist to disseminate science to children and the aspects of the science communication genre for children that are present in the letters. The didactic discourse, aspects such as the playful dimension, humor, transgression, and interpellation, with a use of words that bring the presumed public closer to scientific content, stand out in Einstein's letters. The existence of Einstein's letters remains a rare example of contact from a renowned scientist who proposes to dialogue with children.